Diseño de un sistema de gestión de calidad para el área de hematología y coagulación del laboratorio clínico del Hospital Isidro Ayora, de acuerdo a la norma ISO 9001-2015 - Yaguache Duarte, Josselyn Cristina (2022)
The objective of this work is to design a quality management system (QMS) based on the ISO 9001-2015 international standard for the hematology and coagulation areas of the Clinical Laboratory of the Hospital Isidro Ayora, to find the objectives, a cross-sectional, descriptive and quantitative approach study was conducted. The work was carried out in two stages: in the first stage the situational status of the laboratory was verified with a checklist based on the requirements established by the ISO 9001-2015 standard, a compliance of 59% was determined, a partial compliance of 8% and a non-compliance of 33%, subsequently, with the analysis of the results obtained the QMS proposal was planned and designed, for this the documents that evidence the QMS were updated and developed, among them: document preparation guide, the quality manual, the procedures manual and other corresponding records. With the implementation of the standard, the clinical laboratory will be able to provide a better service, increasing the quality and safety of the services, for the satisfaction and expectations of the clients